Identifying Factors Influencing the Design of a Suitable Knowledge Base in Product Engineering Projects. (May 2022) - Kempf, C.; Sanke, F.; Heimicke, J.; Rapp, S.; Albers, A.
Abstract: During product engineering, engineers draw on existing knowledge as a basis. This knowledge is applied in design processes either by adopting elements, alternating some attributes, or changing the solution principles. While concepts for design reuse exist, the proactive design of a suitable knowledge base is still a challenge. In this paper, we show influencing factors in engineering and their influence on the knowledge base. These factors are of the areas market, company, project, and team. Based on our results, we intent to develop a support for engineers to set up the knowledge base.